Evaluating the Effectiveness of Environmental Legal Instruments in Addressing Inequality of Clean Water Access in Multicultural Rural Communities - Aziz Widhi Nugroho; Martitah Martitah; Dede Rusmana (Green Social: International Journal of Law and Civil Affairs, 2025)
Rapid This study examines the effectiveness of environmental legal instruments in addressing water access inequalities in multicultural rural communities. Despite the existence of various legal frameworks, disparities in water access remain prevalent, especially in rural areas where socio economic, cultural, and governance challenges persist. Legal instruments such as the Water Framework Directive (WFD) and the Clean Water Act (CWA) have proven effective in improving water quality and access in urban settings, but their impact in rural communities is often limited. The study explores the role of legal pluralism, where both statutory and customary laws coexist, in enhancing water governance. It also evaluates the importance of integrating cultural sensitivity into legal frameworks to foster community participation and sustainable water management. Through a mixed methods approach combining legal analysis and socio economic assessments, this study provides insights into the barriers to effective water governance and proposes policy recommendations for improving water access. Key findings suggest that inclusive governance models, which respect local customs and empower communities, lead to more sustainable and equitable water management outcomes. The study highlights the need for legal reforms that recognize the diverse cultural, governance, and infrastructural contexts of rural communities, ensuring that water access policies are both culturally adaptive and legally effective. By integrating these approaches, future policies can more effectively tackle water access inequalities in multicultural rural settings.